2022
DOI: 10.3390/computers11090135
|View full text |Cite
|
Sign up to set email alerts
|

Vertical Farming Perspectives in Support of Precision Agriculture Using Artificial Intelligence: A Review

Abstract: Vertical farming is a new agricultural system which aims to utilize the limited access to land, especially in big cities. Vertical agriculture is the answer to meet the challenges posed by land and water shortages, including urban agriculture with limited access to land and water. This research study uses the Preferred Reporting for Systematic Review and Meta-analysis (PRISMA) item as one of the literary approaches. PRISMA is one way to check the validity of articles for a literature review or a systematic rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 64 publications
0
21
0
2
Order By: Relevance
“…With the rapid advancement of digital technologies, IoT devices, artificial intelligence, and other cutting-edge technologies are increasingly being incorporated into VF. According to Siregar et al [51], IoT devices and AI are being employed to monitor and control VF environments, and researchers such as those found in [52][53][54] have proposed methodologies that integrate sensors and IoT techniques for smart VF. Additionally, Kaur et al [55,56] demonstrated how hydroponic VF could be carried out using IoT-based sensors with minimal water and soil usage.…”
Section: Vertical Farming and Smart Greenhousementioning
confidence: 99%
“…With the rapid advancement of digital technologies, IoT devices, artificial intelligence, and other cutting-edge technologies are increasingly being incorporated into VF. According to Siregar et al [51], IoT devices and AI are being employed to monitor and control VF environments, and researchers such as those found in [52][53][54] have proposed methodologies that integrate sensors and IoT techniques for smart VF. Additionally, Kaur et al [55,56] demonstrated how hydroponic VF could be carried out using IoT-based sensors with minimal water and soil usage.…”
Section: Vertical Farming and Smart Greenhousementioning
confidence: 99%
“…Further, it is noticed that various survey work is carried out towards addressing various PA-based issues via. Privacy (Demestichas et al [101], Gupta et al [102]), control strategies in PA (Hassan et al [103]), emerging technologies in PA (Mesías-Ruiz et al [104], Singh et al [105]), ML-based approaches (Benos et al [106], Sharma et al [107]), ML approaches for pest and disease identification (Domingues et al [108]), IoT based approaches (Dhanaraju et al [109]), AI-based approaches for vertical farming (Holzinger et al [110], Siregar et al [111]), DL-based approaches used in PA (Altalak et al [112]). However, it has been noted that some review works have emphasized IoT-based deployment approaches towards PA [113]- [119].…”
Section: Research Gapsmentioning
confidence: 99%
“…Saat ini, algoritma Learning Vector Quantization (LVQ) sebagai bagian pendekatan teknik Machine Learning (ML) telah banyak di implementasikan pada penelitian berbagai bidang di antaranya teknik lingkungan [1], [2], pembelajaran online semi-supervised [3], [4], pengenalan wajah [5] hingga pertanian [6], [7]. Deteksi dan klasifikasi adalah salah satu topik yang menarik dan banyak dibahas pada penelitian di bidang ilmu komputer.…”
Section: Pendahuluanunclassified